1976
DOI: 10.1021/bi00649a003
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analysis of DNA. XXIV. Synchronous digestion of SV40 DNA by exonuclease III

Abstract: We have established an optimal condition for the synchronous digestion of SV40 DNA with Escherichia coli exonuclease III. Electron microscopy and polyacrylamide gel electrophoresis were used to obtain accurate measurements on the lengths of DNA before and after exonuclease III digestion. Based on this finding, a new method for determining the sequence of long duplex DNA can be realized. It involves (a) the synchronous digestion of the DNA from the 3' ends with exonuclease III, followed by (b) repair synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Furthermore, Yajko and Weiss (1975) have shown that point mutations in the xth structural gene led to a concomitant loss of both the endonucleolytic and exonucleolytic activities, suggesting that both the endonucleolytic and exonucleolytic activities may be sharing the same active site. Therefore, it has been assumed A .…”
Section: Mechanism Of Action Of Exonuclease III a Modifiedmentioning
confidence: 99%
“…Furthermore, Yajko and Weiss (1975) have shown that point mutations in the xth structural gene led to a concomitant loss of both the endonucleolytic and exonucleolytic activities, suggesting that both the endonucleolytic and exonucleolytic activities may be sharing the same active site. Therefore, it has been assumed A .…”
Section: Mechanism Of Action Of Exonuclease III a Modifiedmentioning
confidence: 99%
“…Two different schemes are currently employed for progressively varying the length of double-stranded DNA fragments. One is the use of exonuclease III followed by single-strand-specific S1 nuclease (1,2,4,5,7,8). Another scheme uses Bal 31 nuclease (3, 6), which simultaneously digests both 5' and 3' ends of a doublestranded DNA fragment (9).…”
mentioning
confidence: 99%
“…It had been determined that Exo III digested in processive and synchronous (when added in excess) manners (17) and was demonstrated to remove up to 14.4 kb DNA sequence during 32 min incubation at 37°C (18). However, phosphorothioate linkages were resistant to Exo III (16) which should have ensured the ''safety'' of Oligo1-ligated template DNA.…”
Section: Resultsmentioning
confidence: 99%